THE INFLAMMATORY REACTION OF PULP TISSUE WITH CALCIUM HYDROXIDE, MTA AND PORTLAND CEMENT (In Vivo) - Jos Erry Hesti Witasari; Usman Munyati; Anggraini Dewi (Odonto : Dental Journal, 2017)
Background : Perforation in normal pulp could be happened anytime. In sterile condition, direct pulp capping was the right therapy to maintain the vitality and pulp function. Direct pulp capping agent must contact with the pulp tissue. Generally, body had an immunologic respond with foreign body that contact with tissue. The respond could be inflammatory reaction. The used direct pulp capping agents were calcium hydroxide, and Mineral Trioxide Aggregate (MTA) which known as better agent but relatively expensive and difficult to obtain. So that, the alternative of MTA, Portland cement which was the same essential of MTA, was being developed. The aim of this study, to analized inflammatory reaction of the pulp tissue with direct pulpcapping agents calcium hydroxide, MTA, and Portland cement.Methods: Free caries M. Nemestrina’s posterior teeth were prepared to formpin point perforations on buccal surface of the crowns. The teeth were appliedwith one of the three capping agents. Teeth were filled and extracted. Theextracted teeth were proceed into histopatological preparation slides to evaluatethe inflammatic reaction.Results: The result showed no statistically significant differences of pulp inflammatory reaction between calcium hydroxide, MTA and Portland cement in7, 14, 42, and 90 days.Conclusion: The inflammatory reaction of pulp tissue of the three pulp cappingagent (calcium hydroxide, MTA, and PC) were insignificant different.